A clinical study on amoebic liver abscess (Bangladesh Journal of Medical Science, 2014)
Background: Amoebic liver abscess presents with severe pain and high grade fever and if not diagnosed and treated promptly, may lead to complications and mortality. Aim and objectives: The objective of the present study was to estimate the incidence, need for aspiration and prognosis. The diagnosis was based on clinical features, positive Elisa test, ultrasonography, aspiration of anchovy sauce from the liver lesion, isolation of E. Histolytica (cyst/trophozoite) from the stool of the patient. Result: We had 65 cases in the study. There were 52 males & 13 females with a ratio of 4:1. Solitary abscess was found in 48 (73.8%) patients which are located as follows; right lobe(43), left lobe(2) and in both lobe(3). 9% were aspirated at presentation due to their size or position. Only 4 (2%) were aspirated at first follow-up on third day due to non resolution of pain or fever or increase in size. All the patients are responded to standard treatment of metronidazole. Amoebic liver abscess is a common diagnosis in our setup. Conclusion: Clinical background and sonogram give a reasonable suggestion about amoebic etiology. If initial aspiration is not indicated due to size larger than 10 cm or proximity to surface, conservative treatment with oral or intravenous metronidazole is successful. DOI: http://dx.doi.org/10.3329/bjms.v14i1.15525 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.49-52